Os nós da docência: as vivências escolares de docentes e jovens alunos permeadas pelo ensino de Sociologia - Marcos Antonio Silva (2016)
This dissertation seeks to describe and understand how the relations of young students and teachers are intermediated by the Teaching of Sociology, in two schools of the Metropolitan Region of Belo Horizonte. Thus, the interaction between Teaching Sociology and its main subjects (young students and teachers) in the school environment was the starting point of this research. For this, three insertions were made in the theme where, in a first moment, the history, the intentions and the intentions of the Teaching of Sociology in the basic education in the current Brazilian educational context were delimited. Next, we seek to construct a genealogy of the trajectories of the two teachers participating in the research, with the purpose of evidencing the origin of values, principles and practices adopted when working with teachers of sociology in the Public Education Network of the State of Minas Gerais. Finally, we sought to analyze the perspectives that the young students of the two groups that participated in the research had in front of the school environment and the teaching of sociology, and the teacher / young student relationship in the classes of this discipline. From the authors of the sociology of education (TARDIF, DUBET, TEIXEIRA) and youth sociology (FANFANI, DAYRELL), we present a theoretical-methodological path that prioritizes the dialogue of the perspectives of the subjects involved in the research with the theoretical frameworks, which guided Our analyzes. Thus, in this investigation, we were able to verify the impact of the relational component on the teacher education of the teachers analyzed and on the teacher / young student relationship in the sociology classes, noting how this factor influences the learning process of its contents, Relation to the classes analyzed.